INSERTIONAL CODE MIXING BY THE ENGLISH DEPARTMENT STUDENTS IN PUTERA BATAM UNIVERSITY - Nurma Dhona Handayani; Robby Satria (English Language Teaching and Research, 2017)
This research discusses the types of code-mixing based on the characteristics of insertion. Mixing of the language is the insertion of a word or phrase of one language to other language where one language as a base or matrix language. A person who has mixed is if he or she uses a word or phrase from another language. Otherwise, the phenomenon of mixing occurs, if a person uses one clause which has the grammatical structure of one language and after that, it is constructed based on the grammar of another. The phenomena of code-mixing can also occur in English students’ communication. Therefore, this research aims to find out what are the characteristics of code-mixing insertion found in the utterances of English Department students in Putera Batam University. Data were collected by using a non-participant observation, recording techniques and transcription. Analysis of the data refers to the Musyken’s code-mixing typology toward the utterances between Indonesian and English. After analyzing the data, there are two insertional code mixing found, single constituent and morphological integration. Single constituent occurs dominantly because the habit of the student in replacing some of words in English into Bahasa Indonesia. Morphological integration happens when the students tend to add affixation into some words in English thus the possibility of insertion created frequently. Key words: Code mixing, single constituent, morphological integration.